2011
DOI: 10.1128/iai.01142-10
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis Uses Distinct Mechanisms of Biofilm Formation To Interfere with Phagocytosis and Activation of Mouse Macrophage-Like Cells 774A.1

Abstract: Assembly of adherent biofilms is the key mechanism involved in Staphylococcus epidermidis virulence during device-associated infections. Aside from polysaccharide intercellular adhesin (PIA), the accumulation-associated protein Aap and the extracellular matrix binding protein Embp act as intercellular adhesins, mediating S. epidermidis cell aggregation and biofilm accumulation. The aim of this study was to investigate structural features of PIA-, Aap-, and Embp-mediated S. epidermidis biofilms in more detail a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 50 publications
(73 reference statements)
6
137
1
1
Order By: Relevance
“…Multiples studies also have demonstrated a fitness defect resulting from decreased resistance to the host immune response in PIA-negative strains (15,94); however, this difference is negated in our model as a consequence of CP treatment. Additionally, as S. epidermidis produces few virulence factors, the tissue damage observed in the PIA-producing strain most likely was a consequence of the host immune response that again would not be expected in our model due to the severe CP-induced immunosuppression (76) (see Fig.…”
Section: Figcontrasting
confidence: 46%
See 1 more Smart Citation
“…Multiples studies also have demonstrated a fitness defect resulting from decreased resistance to the host immune response in PIA-negative strains (15,94); however, this difference is negated in our model as a consequence of CP treatment. Additionally, as S. epidermidis produces few virulence factors, the tissue damage observed in the PIA-producing strain most likely was a consequence of the host immune response that again would not be expected in our model due to the severe CP-induced immunosuppression (76) (see Fig.…”
Section: Figcontrasting
confidence: 46%
“…S. epidermidis biofilm matrix composition varies between strains and may be composed of a combination of polysaccharide (polysaccharide intercellular adhesin; PIA), proteins (e.g., accumulation-associated protein [Aap] and extracellular matrix-binding protein [Embp]), and/or extracellular DNA (eDNA) (2,(10)(11)(12)(13)(14). Although these components have unique structural characteristics, PIA-, Embp-, and Aap-dependent biofilms all are resistant to phagocytosis due to their ability to inhibit NF-B activation and interleukin-1␤ (IL-1␤) production (15,16). Recently, it also was demonstrated that S. aureus biofilms skew the immune response, generating alternatively activated macrophages (17,18) that promote a fibrotic rather than bactericidal response, thereby facilitating bacterial persistence.…”
mentioning
confidence: 99%
“…Immunostaining-Localization of GAS bacteria during infection of the macrophage cell line MH-S or primary macrophages was determined using the double-fluorescence immunostaining method described previously (20,21). This method is based on the application of two different fixation methods.…”
Section: Quantification Of Gas Inside or Outside Of Macrophage Cells mentioning
confidence: 99%
“…Staphylococcus epidermidis is recognized as a leading nosocomial pathogen. This microorganism has a strong ability to establish adherent biofilms on artificial surfaces such as central venous catheters, artificial heart valves, and prosthetic joints [36].…”
Section: Introductionmentioning
confidence: 99%